2017
DOI: 10.1039/c7ob00660h
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction in oligoamide foldamers by selective non-covalent binding of chiral phosphates at a urea binding site

Abstract: Non-covalent interactions between a chiral phosphate anion and a urea binding site induce a conformational preference in an amide foldamer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…[47][48][49] Finally, there are various examples throughout organocatalysis, in which the substrate binding and activation via a hydrogen bonded species is proposed. [50][51][52][53][54] However, the central hydrogen-bonded species are oen in fast chemical exchange or have short lifetimes, therefore it is for most of the systems experimentally not possible to detect these hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Finally, there are various examples throughout organocatalysis, in which the substrate binding and activation via a hydrogen bonded species is proposed. [50][51][52][53][54] However, the central hydrogen-bonded species are oen in fast chemical exchange or have short lifetimes, therefore it is for most of the systems experimentally not possible to detect these hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Having demonstrated that pH-induced exchange of metalbound ligands could be used as a mechanism for the conformational communication of information, we next used it to induce a more extensive conformational change by relaying the induced conformation of the BQPA ligand into an induced screw-sense preference in a pendent foldamer. Complex Zn(8)•2ClO4 was synthesised (see the ESI), in which the achiral helical tetramer of the quaternary amino acid Aib 48 was ligated at its N-terminus to the Zn(1) binding site, and at its C terminus Please do not adjust margins Please do not adjust margins to a fifth (R)-Aib* residue that was enantioselectively labelled with 13 C in its pro-R enantiotopic methyl groups. 49 Peak separation in the 13 C-NMR spectrum allows such Aib* residues to act as reporters of local conformation, 50 thus indicating that pH has been translated into a conformational change and relayed to a remote site.…”
Section: Communicating the Conformational Response To A Spatially Rem...mentioning
confidence: 99%
“…'Universal' indicators function through protonation of a series of indicators of increasing pKa, allowing the concentration of protons to be translated into a colorimetric output. 10 Artificial signalling systems have been designed with more biomimetic features such as spatial communication to remote sites, [11][12][13] agonist/antagonist functions, 14,15 and the ability to operate in the membrane phase. [16][17][18][19]…”
Section: Introductionmentioning
confidence: 99%
“…The development of supramolecular systems [1][2][3][4][5][6][7] able to switch between two or more different states by the effect of external stimuli is an attractive goal of supramolecular chemistry. [8][9][10] Stimuli-controllable multi-functional supramolecular systems emerge when each state features different properties and/or functions such as morphology,a ggregation, and molecular recognition. [11][12] To this end, light and heat are ideal external stimuli because they can produce the switching withouta ddition of external chemicals peciestot he systems.…”
Section: Introductionmentioning
confidence: 99%
“…The development of supramolecular systems able to switch between two or more different states by the effect of external stimuli is an attractive goal of supramolecular chemistry . Stimuli‐controllable multi‐functional supramolecular systems emerge when each state features different properties and/or functions such as morphology, aggregation, and molecular recognition .…”
Section: Introductionmentioning
confidence: 99%